Green Leadership: Kepribadian Ekstraversi, Kecerdasan Lingkungan dan Perilaku Ramah Lingkungan - Constantinus Constantinus; Dian Wishnu Brata; Lisa Ardaniyati (Fakultas Psikologi, Universitas Putra Indonesia YPTK Padang, 2022)
A company needs special attention regarding green leadership. This study aims to produce a green leadership model in profit-oriented companies. The research was conducted using quantitative methods in a Limited Liability Company (Perseroan Terbatas / PT) Rural Bank (Bank Perkreditan Rakyat / BPR) Restu Artha Makmur, headquartered in the city of Semarang. The study was conducted on June 22, 2022 with 107 (one hundred and seven) respondents consisting of staff, supervisors, and managers. Empirical data were analyzed using the AMOS statistical tool, and gave the results in the form of an empirical model of path analysis 1 is GL = 0.585 E + 0.190 KL + 0.390 PRL + e1 (R2 = 0.624), where GL is Green Leadership, E is Extraversion Personality (kepribadian Ekstraversi), KL is Environmental Intelligence (Kecerdasan Lingkungan), and PRL is Pro-Environmental Behavior (Perilaku Ramah Lingkungan) in the context of the company. The empirical model of path 2 analysis is PRL = 0.261 E + 0.529 KL + e (R2 = 0.556). The results showed that Extraversion Personality (E) had a significant positive effect on Pro-Environmental Behavior (PRL), and Environmental Intelligence (KL) had a significant positive effect on Pro-Environmental Behavior (PRL). In addition, the results of the study also show that Extraversion Personality (E) has a significant positive effect on Green Leadership (GL), while Environmental Intelligence (KL) has a positive but not significant effect on Green Leadership (GL), as well as Pro-Environmental behavior (PRL) positive but not significant effect on Green Leadership (GL). Thus, Pro-Environmental Behavior (PRL) does not mediate the effect of Extraversion Personality (E) and Environmental Intelligence (KL) on Green Leadership (GL).